If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 5) = 2(3x) + 14 Reorder the terms: 4(5 + x) = 2(3x) + 14 (5 * 4 + x * 4) = 2(3x) + 14 (20 + 4x) = 2(3x) + 14 Remove parenthesis around (3x) 20 + 4x = 2 * 3x + 14 Multiply 2 * 3 20 + 4x = 6x + 14 Reorder the terms: 20 + 4x = 14 + 6x Solving 20 + 4x = 14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + 4x + -6x = 14 + 6x + -6x Combine like terms: 4x + -6x = -2x 20 + -2x = 14 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + -2x = 14 + 0 20 + -2x = 14 Add '-20' to each side of the equation. 20 + -20 + -2x = 14 + -20 Combine like terms: 20 + -20 = 0 0 + -2x = 14 + -20 -2x = 14 + -20 Combine like terms: 14 + -20 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| Cos22°(3/5) | | -1/8(3/5) | | y=0.0006x+1E-17 | | -5d-3.5d=26.5 | | 20-(x+9)=6x-3 | | 5s+27=172 | | x^2-14x-53=0 | | -3/5*-1/9 | | 2-n=-1 | | t+12=12 | | 25.56+x=25.72 | | 14-3f=2 | | x-10=3x-12 | | -2-n=0 | | 90=-2(3-6k) | | 3r+19=4-2r | | logx=0.32 | | 2(x+6)=3(x+7) | | x+1=12x-1 | | 3/5*(-1/6) | | 3r/10=6 | | -2.73+x=-.3 | | q/-5=18 | | 2log(3x+5)=4 | | -19.5=9.5x-5.5x | | 12(x+1)=-3 | | 22=x-7.8 | | 14-5x=-52 | | 121=4x+7 | | 4(x-5)=2(x+2) | | x+15+75=x | | (x-lnx*2x)/x^4 |